Effect of Salvia hispanica L. (chia) on the physicochemical characteristics and antioxidant capacity of the Physalis peruviana drink (aguaymanto) - Chagua Rodriguez, Perfecto (2020)
The importance of the consumption of functional drinks made from promising fruits goes through their nutraceutical contribution, which is essential for human health. The objective of the present investigation was to elaborate a functional drink from aguaymanto (Physalis peruviana) and chia (Salvia hispanica L.), for its subsequent evaluation of the physicochemical characteristics and antioxidant activity. Aguaymanto and chia were from the province of Acobamba, Huancavelica-Peru. For the analytical determinations, 04 treatments (T) of functional drink (BF) were conditioned: T1 = BF + 0.0% of chia, T2 = BF + 0.5% of chia, T3 = BF + 1.0% of chia and T4 = BF + 1.5% of chia. For the physicochemical analyzes, methods described by the AOAC were used and for the antioxidant capacity the ABTS+ radical. Aguaymanto functional drink managed to increase its physicochemical characteristics and antioxidant activity from the incorporation of chia. The antioxidant activity of the functional drink without chia express 0.62 µmol of Eq. Trolox / mL (ABTS inhibition), the addition of chia caused its increase to 1.45 µmol of Eq. Trolox / mL. It is concluded that the incorporation of chia into the functional aguaymanto drink generates a significant increase in nutraceutical qualities, obtaining a food with high antioxidant potential.